Experimental Demonstration of Ultra-Dense WDM-PON With Seven-Core MCF-Enabled Self-Homodyne Coherent Detection - Chunxiao Xiong; Ming Tang; Changjian Ke; Zhenhua Feng; Qiong Wu; Liang Xu; Songnian Fu; Weijun Tong; Perry Ping Shum; Deming Liu (IEEE Photonics Journal, 2017)
We demonstrate an ultra-dense wavelength-division-multiplexing (UDWDM) passive optical network (PON) in a spatial-division-multiplexing system utilizing our home-made seven-core multicore fiber (MCF) with a self-homodyne coherent detection (SHCD) scheme. In the SHCD system, we transmit 12 channels of 40-Gb/s UDWDM-PON signals using polarization-division-multiplexing quadrature phase-shift keying (PDM-QPSK) with a 12-GHz grid through the six outer cores of the seven-core MCF with the central core used to transmit the pilot tone. An optical frequency comb generator is employed to supply the multi-carriers for cost saving. After 37-km low-crosstalk seven-core MCF long-reach transmission with compact fan-in/fan-out multiplexers, a large transmission capacity of 2.88 Tb/s and a power budget of 26 dB are obtained. At the optical network unit side, a narrow linewidth local oscillator laser is no longer necessary since SHCD is adopted in our system. The complexity of the digital signal processing procedure at the coherent receiver is also greatly reduced as the carrier phase recovery and carrier frequency offset estimation are not needed.